Decreased Nitrogen and Carbohydrate Metabolism Activity Leads to Grain Yield Reduction in Qingke Under Continuous Cropping - Zhiqi Ma; Chaochao He; Jianxin Tan; Tao Jin; Shuijin Hua (Plants, 2025)
Qingke (Hordeum vulgare L. var. nudum Hook. f.), a staple crop in the Tibetan Plateau, suffers from severe yield reduction under continuous cropping (by 38.67%), yet the underlying mechanisms remain unclear. This study systematically investigated the effects of 23-year continuous cropping (23y-CC) on the nutrient dynamics, carbohydrate metabolism, and enzymatic activities in Qingke leaves across five developmental stages (T1: seedling; T2: tillering; T3: jointing; T4: flowering; T5: filling). Compared to the control (first-year planting), 23y-CC significantly reduced leaf nitrogen (N), phosphorus (P), and potassium (K) contents by 60.94%, 47.96%, and 60.82%, respectively, at early growth stages. Key nitrogen-metabolizing enzymes, including glutamate synthase (GOGAT), glutamine synthase (GS), and nitrate reductase (NR), exhibited reduced activities under 23y-CC, indicating impaired nitrogen assimilation. Carbohydrate profiling revealed lower starch and glucose contents but higher sucrose accumulation in later stages (T4–T5) under 23y-CC, accompanied by the dysregulation of sucrose synthase (SS) and invertase activities. These findings elucidate how continuous cropping disrupts nutrient homeostasis and carbon allocation, ultimately compromising Qingke productivity. This study provides novel insights into agronomic strategies for mitigating continuous cropping obstacles in Qingke.